Gender and Polysomnographic Profiles Findings in Obstructive Sleep Apnea Syndrome Patients Living in High Altitude - Patiño MC (Dove Medical Press, 2021)
Marcela Concha Patiño,1 Silvia Juliana Bueno Florez,2 Loren Gallo,3 Paola Andrea Ortiz,2,4 César Payán-Gómez,5 Nicolas Molano-Gonzalez,6 Jesús Hernán Rodríguez2– 4,7 1Department of Neurology, Clinica Nueva Rafael, Cali, Valle del Cauca, Colombia; 2Department of Neurology, Fundación Cardioinfantil, Bogotá, Cundinamarca, Colombia; 3Department of Neurology, Hospital Mederi, Bogotá, Cundinamarca, Colombia; 4Grupo de Neurociencias de la Universidad del Rosario (NEUROS), Universidad del Rosario, Bogotá, Cundinamarca, Colombia; 5Department of Biology, Faculty of Natural Sciences, Universidad del Rosario, Bogotá, Colombia; 6Clinical Research Group, School of Medicine and Health Sciences, Universidad del Rosario, Bogotá, Cundinamarca, Colombia; 7Neurology department, School of Medicine and Health Sciences, Bogotá, Cundinamarca, ColombiaCorrespondence: Nicolas Molano-GonzalezClinical Research Group, School of Medicine and Health Sciences, Universidad del Rosario, Carrera 23 # 63a-40, Bogotá D.C, 111221, ColombiaTel +(571)297 0200 Ext. 3400Email nicolas.molano@urosario.edu.coPurpose: Obstructive sleep apnea (OSA) is a common sleep disorder which prevalence is 22% in men and 17% in women. It is well described that females presented different clinical and polysomnographic characteristics compared with men. Those studies were performed in plain areas. We described the analysis by gender and clinical profiles of a sample of patients with diagnostic of OSA and living at high altitude.Patients and Methods: It is an observational study that describes differences between clinical and polysomnographic characteristics by gender in patients with OSA. Additionally, an unsupervised cluster algorithm was used to find groups of patients with similar clinical and polysomnographic characteristics.Results: We included 709 patients, 51.6% were females and 48.3% were males with mean age of 64 and 62 years old, respectively, in which 90.97% presented OSA. Men presented a higher apnea and hypopnea index than women (p=0.002), besides presented more sleep polysomnographic alterations. Meanwhile, women evidenced better sleep quality based on parameters. Additionally, in the sample of patients, we found four separated clinical profiles characterized mainly by differences in the severity of polysomnographic parameters.Conclusion: The patients were more obese, older, and had lower SpO2 values than most of those previously reported. Men had greater severity in most of the parameters measured by polysomnography. Polysomnographic variables were different both in the OSA patient profiles and in the gender comparison. However, the REM sleep apnea hypopnea index did not differ between sexes, indicating the importance of this variable in the evaluation of OSA severity in women. In contrast to previous reports, clinical and demographic characteristics showed few differences in both analyses. This result suggests that the behavior of OSA at high altitudes may have particularities with respect to low altitudes.Keywords: sleep-disordered breathing, cluster analysis, altitude, gender identity, sleep monitoring